ZnO–graphene–polyaniline nanoflowers: solution synthesis, formation mechanism and electrochemical activity. Issue 47 (25th April 2016) - Bera, Susanta; Naskar, Atanu; Pal, Moumita; Jana, Sunirmal
Abstract : Morphology dependent electrochemical activity of conducting ZnO–graphene–polyaniline nanocomposite. Abstract : Three dimensional hierarchical inorganic–organic hybrid nanoflowers of conducting ZnO–chemically converted graphene–polyaniline nanocomposite have been successfully synthesized at low temperature from surfactant-free precursor solution and studied their formation mechanism. The nanocomposite with hierarchical architecture shows an enhanced electrochemical activity, illustrating a promise for application in electrochemical devices.